Potential Clinical Application of Analysis of Bisphenols in Pericardial Fluid from Patients with Coronary Artery Disease with the Use of Liquid Chromatography Combined with Fluorescence Detection and Triple Quadrupole Mass Spectrometry - Tomasz Tuzimski; Szymon Szubartowski; Janusz Stążka; Kamil Baczewski; Daria Janiszewska; Viorica Railean; Bogusław Buszewski; Małgorzata Szultka-Młyńska (Molecules)
Bisphenols may negatively impact human health. In this study, we propose the use of HPLC–FLD for the simultaneous determination of bisphenols in pericardial fluid samples collected from patients with coronary artery disease undergoing coronary artery bypass surgery. For sample preparation, a fast, simple, and ”green” DLLME method was used, achieving mean recovery values in the range of 62%–98% with relative standard deviations between 2% and 6% for all analytes. Quantitative analysis of bisphenols in the samples was then performed by LC–MS/MS on a triple quadrupole (QqQ) mass spectrometer and electrospray ionization (ESI-/ESI+) was applied in the negative and positive ion modes, respectively. The LODs and LOQs ranged from 0.04 ng/mL to 0.37 ng/mL and 0.12 ng/mL to 1.11 ng/mL, respectively. Pericardial fluid was collected from patients with coronary artery disease during coronary artery bypass surgery. Bisphenol residues were identified and quantified in samples from 19 patients. The procedure was successfully applied to the biomonitoring of free forms of 14 bisphenols in pericardial fluid. After statistical examination of the relationships between the selected variables, a strongly positive correlation was found between creatinine kinase and troponin I, as well as the number of venous anastomoses, circulation time, and clamp cap time.